Widespread Rapid Quenching at Cosmic Noon Revealed by JWST Deep Spectroscopy - Minjung Park; Sirio Belli; Charlie Conroy; Benjamin D. Johnson; Rebecca L. Davies; Joel Leja; Sandro Tacchella; J. Trevor Mendel; Chloë Benton; Letizia Bugiani; Razieh Emami; Amir H. Khoram; et al. (The Astrophysical Journal)
Massive quiescent galaxies in the young Universe are expected to be quenched rapidly, but it is unclear whether they all experience starbursts before quenching and what physical mechanism drives rapid quenching. We study 14 massive quiescent galaxies ( $log(M_{\star }/M_{\odot })\gt 10$ ) at z ∼ 2 selected from a representative sample of the Blue Jay survey. We reconstruct their star formation histories (SFHs) by fitting spectral energy distribution models to the JWST/NIRSpec R ∼ 1000 spectra. We find that massive quiescent galaxies can be split into three categories with roughly equal numbers of galaxies according to their SFHs: (1) relatively old galaxies quenched at early epochs; (2) galaxies that are rapidly and recently quenched after a flat or bursty formation history (depending on the assumed prior); and (3) galaxies that are rapidly and recently quenched after a major starburst. Most recently quenched galaxies show neutral gas outflows, probed by blueshifted Na i D absorption, and ionized gas emission, with line ratios consistent with active galactic nucleus (AGN) diagnostics. This suggests that AGN activity drives multiphase gas outflows, leading to rapid quenching. By tracing back the SFHs of the entire sample, we predict the number density of massive quiescent galaxies at z = 4–6: n = (1.5–6.0) × 10 ^−5 Mpc ^−3 . The two old massive quiescent galaxies in our sample appear to have extremely early formation and quenching ( z ≳ 6) and are possibly descendants of early post-starbursts at z > 3. These galaxies still show neutral gas reservoirs and weak H α emission, perhaps because the ejective AGN feedback that caused rapid quenching has weakened over time.